Investigating the Effect of Rational Emotional Behavioral Therapy Training on Sensitivity in Women’s & Mutual Relationships - Mohammad Taghipour; Neda Ghiasvand (International Journal of Behavioral Sciences, 2024)
The topic of Haaz's research is to investigate the effect of rational-emotional behavioral therapy training on sensitivity in women's mutual relationships. The purpose of this research is to prepare and compile a program in which the concepts of the rational-emotional behavioral therapy approach are used in order to investigate sensitivity in women's mutual relationships after the implementation of its training to women. The statistical population includes 120 women with risky sexual behaviors and a history of substance abuse. Among 120 people according to Morgan's table, 92 people were selected for the sample size, and out of these 92 people, 30 people who got the lowest score in the test were randomly selected and were selected in the experimental and control group. During 10 sessions, the experimental group was given trainings not related to the topic of research on safe sex. The exams were retaken on both groups in the same position following the sessions in order to assess the impact of the independent and dependent variables. The data was analyzed using the covariance statistical model (MANCOVA) and its results and a significant relationship (P < 0.01) showed that the training of rational-emotional behavioral therapy on sensitivity in the mutual relationships of women with high-risk sexual behavior and a history of abuse of the material is effective. This research highlights the effectiveness of targeted behavioral therapy in enhancing interpersonal sensitivity and fostering healthier relationships within this vulnerable group.
Keywords: Behavior training; Sensitivity; drug abuse history; mutual relations of women; substance abuse